Burnout, anxiety and depression in teaching: A study with public school teachers in southern Brazil (Revista Contexto & Educação, 2026)
This study aimed at both verifying the prevalence of burnout, anxiety and depression among elementary school teachers in the school system of the city of Bagé (RS) and examining the association between these variables. A cross-sectional study was carried out with 221 teachers, with the use of a self-administered questionnaire with Profile Form, Maslach Burnout Inventory (MBI) and Hospital Anxiety and Depression Scale (HADS). The results have shown that 6.8% of the participants had burnout, 22.1% had symptoms of anxiety and 14.5% of depression. It was also found that the prevalence of burnout may be directly related to the levels of anxiety and depression among teachers (p
Keywords: Teacher health; Teaching work; School